Hepatocellular carcinoma therapy based on human amniotic membrane - Alves, Andreia Pereira (2018)
The hepatocellular carcinoma is the most frequently detected primary malignant liver tumor, representing a worldwide public health problem due to its morbidity and mortality rates. The high mortality rate is in part due to the late stage at which is diagnosed and its high resistance to conventional therapies, such as radiotherapy and chemotherapy. For this reason, it is very important to find new and effective therapies for hepatocellular carcinoma. The human amniotic membrane (hAM) has been referenced in several publications as a potential therapeutic option in cancer due to its pro-apoptotic, anti-angiogenic and immunoregulatory properties. The hAM-derived cells and their supernatant were already evaluated, in vitro and in vivo, in cancer therapy. In an innovative way, our research group evaluated the protein extracts of human amniotic membrane (hAMPE) in cancer therapy. The extracts were obtained from epithelial and mesenchymal cells, as well as from the extracellular matrix. It was demonstrated that the hAMPE may inhibit the metabolic activity of three human hepatocellular carcinoma cell lines: Hep3B2.1 -7, HepG2 and HuH7. Taking into account the results obtained so far by our research group, associated with the increased glycolytic metabolism in cancer cells, this experimental work aimed to study the effect of hAMPE treatment in the glucose metabolism of hepatocellular carcinoma. It was verified by proton nuclear magnetic resonance (1NMR) that hAMPE treatment increased glucose consumption on Hep3B2.1-7, HepG2, and HuH7 cell lines. However, it was verified that glucose is not converted to lactate. The hAMPE treatment induced similar effects in Hep3B2.1-7 and HepG2, increasing the expression of lactate dehydrogenase (LDH) and monocarboxylate transporter isoform 4 (MCT4), but no changes in lactate levels. Regarding HuH7 cells, the levels of lactate, as well as the expression of LDH and MCT4, decreased in response to hAMPE treatment, suggesting that reduced levels of lactate may indicate a decrease in tumor aggressiveness. This work reveals the anticancer potential of hAMPE, modulating the glycolytic profile of the human hepatocellular carcinoma cells under study. However, further studies are required in order to clarify the relationship between hAMPE treatment and the glycolytic metabolism.